2016
DOI: 10.21474/ijar01/2152
|View full text |Cite
|
Sign up to set email alerts
|

Islamicity and Global Competitiveness: A Cross-Nations Path Analysis

Abstract: This paper analysis the impact, direct and indirect impacts, of Islamicity on Global competitiveness, with Human development as moderator variable. Cross-section data on Islamicity index, Human development index and Global competitiveness index were collected from 123 countries and employed in a path analysis model. The results show that Islamicity had a positive and significant direct impact on global competitiveness. Islamicity had also positive and significant direct impact on human development. These direc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 4 publications
0
1
0
Order By: Relevance
“…His study revealed that Islamicity had a favorable and significant direct impact on global competitiveness. 19 Moreover, Muchdie investigated the linkage and impact of Islamicity on happiness, with human development and global competitiveness as moderating variables. The study displayed a robust relationship among the stipulated variables by using a path analysis model on the data of 123 countries.…”
Section: Literature Reviewmentioning
confidence: 99%
“…His study revealed that Islamicity had a favorable and significant direct impact on global competitiveness. 19 Moreover, Muchdie investigated the linkage and impact of Islamicity on happiness, with human development and global competitiveness as moderating variables. The study displayed a robust relationship among the stipulated variables by using a path analysis model on the data of 123 countries.…”
Section: Literature Reviewmentioning
confidence: 99%